Estudo teórico dos estados de Valência e Rydberg de moléculas da série CF3-nHnCl (n=0-3) - Silva, Vanessa Cristina de Medeiros (2017)
In order to obtain a better understanding of the nature of photochemical processes occurring in the atmosphere, the present work proposed the use of highly correlated computational methods (MCSCF, MRCISD and MR-CISD + Q methods) to analyze geometries, excited states, electronic transitions, dissociation channels, among other aspects of the CF3-nHnCl (n = 0-3) series of molecules, since they are directly related to atmospheric ozone depletion and global warming. The excitation energy calculations obtained with the above methodology provided results consistent with the experimental data. For the CF3Cl molecule, five different dissociative channels were found: (1) CF3 (12A1) + Cl (2P); (2) CF3+ (11A2”) + Cl- (1S); (3) CF3 (22A1) + Cl (2P); (4) CF3 (12E) + Cl (2P); (5) CF3 (32A1) + Cl (2P). The same number of channels was also discovered for the CH3Cl species: (i) CH3 (X 2A2") + Cl (2P), (ii) CH3 (3s2A1') + Cl (2P), (iii) CH3+(1A1') + Cl- (1S), (iv) CH3 (3p2E') + Cl (2P), e (v) CH3 (3p2A2") + Cl (2P). From the study of the potential energy curves, it could be determined how the nonadiabatic events contribute to the ion channel favoring in the CH3Cl molecule and the desactivation of the same channel in the CF3Cl species. Thus, it is concluded that this type of study serves as an important complement to the experimental spectroscopic studies, facilitating in the signaling of electronic transitions.